THE DILEMMA OF ONLINE LEARNING DURING THE COVID-19: CHALLENGES OR OPPORTUNITIES? - Ira Irzawati (Esteem Journal of English Education Study Programme, 2021)
This research aimed to investigate the chalenges and opportunities of online learning system implementation from students' perspectives. In this survey research, 143 students of a  private university were involved as the respondents. The respondents were third, fifth, and seventh-semester students from four different departments that have experienced learning English through an online learning system. The data of the research were gathered through administering  an online  survey  to  the respondents. The survey questionnaire covered items related to demographic information, online learning application, and chalenges and opportunities of online learning. The data of the survey were analyzed by presenting  the  frequency  of  students' responses towards each item of the questionnaire in form of a percentage. The students believed that  online  learning  potentialy  provided  both chalenges and opportunities to the students.  Technical  issues,  minimum  interaction,  low  discipline, and a less effective learning atmosphere were among the dominant chalenges of online learning. Meanwhile, various material access, flexibility, interactive learning, and a relaxing learning atmo sphere were the major opportunities of online learning. Anticipating the chalenges and maximizing the opportunities are alternative solutions to promote the successful implementation of online learning.